Assessing the concurrent validity, inter‐rater reliability and test–re‐test reliability of the Australian Treatment Outcomes Profile (ATOP) in alcohol and opioid treatment populations. (4th January 2021) - Deacon, Rachel M.; Mammen, Kristie; Bruno, Raimondo; Mills, Llewellyn; Dunlop, Adrian; Holmes, Jennifer; Jefferies, Meryem; Hall, Michelle; Shakeshaft, Anthony; Farrell, Michael; Graham, Robert; Lintzeris, Nicholas
Abstract: Background and Aims: The Australian Treatment Outcomes Profile (ATOP) is a brief instrument measuring recent substance use, risk profile and general health and wellbeing among clients attending alcohol and other drug (AoD) treatment services. This study evaluates the ATOP for concurrent validity, inter‐rater and test–re‐test reliability among alcohol and opioid treatment groups. Design: For concurrent validity and inter‐rater reliability, participants completed an ATOP with a clinician and an ATOP plus standardized questionnaires (time‐line follow‐back, Opiate Treatment Index, Kessler‐10, 12‐item Short Form Survey, World Health Organization Quality of Life‐BREF, Personal Wellbeing Index) with a researcher within 3 days. For test–re‐test reliability, participants completed two ATOPs with a researcher within a 3‐day interval. Setting: Outpatient AoD treatment centres in Australia. Participants: For testing concurrent validity and inter‐rater reliability, 278 participants were recruited by advertisements in waiting‐rooms or clinician invitation during 2016 to 2018. A further 94 participants were recruited to examine test–re‐test reliability. Measurements: Statistical tests used for concurrent validity and test–re‐test reliability were Pearson's and Spearman's rank order correlations for continuous variables, and Cohen's κ for nominal variables. Inter‐rater reliability was assessed using Krippendorf's α. Findings: Most Australian Treatment Outcomes Profile items returned excellent or moderate validity and reliability. For the main substances used—alcohol, cannabis and benzodiazepines—concurrent validity, inter‐rater reliability and test–re‐test reliability all reached excellent or good agreement (0.72–0.96). Psychological health, physical health and quality of life showed fair to strong agreement with their comparator scales (0.47–0.85). Conclusions: The Australian Treatment Outcomes Profile is a validated and reliable instrument for assessing recent substance use and clinical risk, health and welfare among alcohol and opioid clients in alcohol and other drug treatment settings. Its ability to reliably measure complex constructs, such as psychological and physical health, against longer scales makes it suitable for integration into routine clinical care, enabling regular monitoring of patient outcomes and safety parameters.